Biophilia, Biodiversity, and the Bible - Brown, William P. (Religions, 2021)
For all its anthropocentric focus on human agency in history and creation, the Hebrew Bible’s valuing of nonhuman life and its diversity cannot be gainsaid among certain traditions. Such is the case in three major creation texts: Genesis 1, Psalm 104, and Job 38-41. Each in its own way, these biblical accounts affirm the intrinsic worth of biodiversity, the expansiveness of life, and a God who values the flourishing of all creation.